As Gravuras Ainda Não Aprenderam a Nadar: impacto das cheias na arte rupestre do Vale do Côa entre 1996 e 2016 - Luís, Luís (2018)
Analysis of the impact of seasonal floods on the rock art of the Côa Park and Museum (UNESCO World Heritage), based on park warden records from 1996-2016. A close study of the relationship between precipitation levels and the river Côa water volume clearly shows that, despite the action of natural agents, the immediate cause of floods is man-made and is a direct consequence of the construction of the cofferdam of the Côa River. Human alteration of the Lower Côa hydrologic system dynamics is the most serious threat to the integrity of the existing rock art.